Design and Evaluation of Smart Digital Signature Application User Interface for Document Legalization in COVID 19 Pandemic - Fitriana, Gita Fadila; Wibowo, Merlinda; Aribowo, Eko (Scientific Journal of Informatics, 2022)
Abstract. Purpose: This study aims to build an effective user interface digital signature application for document legalization.Methods: The process of document publishing services and bureaucratic flows at universities affected by the pandemic can be simplified and accelerated with this application later. However, appropriate application design still needs to be done before application development. Therefore, application design is carried out on the User Interface (UI) to the prototype stage so that the application to be built can be more attractive, more effective, and efficient. In addition, to help the application succeed, it is also necessary to evaluate the design process.  Result: This testing process is carried out to prevent failures from later application development by implementing an easy and frequently used test, namely usability testing, namely the Usability Scale (SUS) System. The tests carried out have shown that the design proposed in this study gets a good score of 80.5, so it is effective and efficient to be implemented and implemented in the development of smart digital signature applications.Novelty: This study is to design and evaluate the UI of the smart digital signature application to provide participation for the success of the application that will be developed later. Therefore, the smart digital signature application can be used effectively and efficiently as a document validation process during this pandemic, which is needed, especially in universities, to improve staff performance and support academic activities. The number of digital documents signed and sent will be the same as the documents received. Furthermore, the validity and integrity of the document can be monitored using the developed application.